2015
DOI: 10.3389/fnbeh.2015.00309
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Different Sub-Regions of the Insular Cortex in Various Phases of the Decision-Making Process

Abstract: This paper presents a coherent account of the role of the insular cortex (IC) in decision-making. We follow a conceptualization of decision-making that is very close to one previously proposed by Ernst and Paulus (2005): that the decision process is a progression of four phases: (1) re-focusing attention; (2) evaluation; (3) action; and (4) outcome processing, and we present evidence for the insula’s role in all these phases. We review the existing work on insula’s functional anatomy that subdivides the IC int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
102
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 105 publications
(150 reference statements)
8
102
0
1
Order By: Relevance
“…This may reflect similar computational processes occurring for harm/welfare-based transgressions and conventional transgressions, potentially involving performance reporting/monitoring (c.f. Droutman et al, 2015; Gratton et al, 2016), but that these occur more strongly for harm/welfare-based transgressions. Two caveats should be noted with respect to this conclusion, however.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This may reflect similar computational processes occurring for harm/welfare-based transgressions and conventional transgressions, potentially involving performance reporting/monitoring (c.f. Droutman et al, 2015; Gratton et al, 2016), but that these occur more strongly for harm/welfare-based transgressions. Two caveats should be noted with respect to this conclusion, however.…”
Section: Discussionmentioning
confidence: 94%
“…The current study was not designed to, and cannot distinguish, between these accounts. However, it is worth noting that there have been recent suggestions that the interactions of dmFC and aIC are differentiable according to the region of aIC involved (Droutman, Bechara, & Read, 2015). In particular, it has been suggested that interactions of dmFC with the more superior region of aIC seen in the current study typically underpin a more attentional role (a more inferior region of aIC is implicated in response control/avoidance; Droutman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dorsal anterior region is functionally connected to the anterior cingulate cortex and dorsolateral prefrontal cortex and is implicated in executive control and higher cognition (31). Notably, the insular cortex is one of the most widely activated neural regions across studies of awareness, emotional experience, craving/urges, and more recently, decision-making (for an elegant review see (33)). Despite this diversity in function, Craig (29) suggests that this is due to the influence of the core function of the insular cortex as an integrative site for autonomic, cognitive, and affective processing.…”
Section: Introductionmentioning
confidence: 99%